ITIKAD BAIK DALAM PERJANJIAN PINJAM MEMINJAM UANG PADA KOPERASI PEGAWAI LEMBAGA PEMASYARAKATAN DI TINJAU MENURUT PASAL 1338 AYAT ( 3) KITAB UNDANG –UNDANG HUKUM PERDATA - Indra Ramadhana (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTBoth parties must be acting in good faith in implementing the agreement. There are times when good faith has been fully carried out and considered, but the implementation of the agreement is still in a deadlock (deadlock). This is where the attention is required towards compliance so that an event can be resolved satisfactorily. Of course, as with any item something that contains award (waardering), compliance is unlikely to result in a settlement of events that satisfy every man, but always is not absolute (relatief), which is worth in the thoughts and feelings of people who are in charge of completing a events, such as the judge or government agency after watching all the factors, which can be used in the minds and the natural feelings of the people that. Occurred close relationship between the doctrine of good faith in the implementation of the agreement and the theory of confidence at the time of the agreement. The good faith (Article 1338 paragraph 3) and propriety (Article 1339) is generally mentioned in the same breath, if the judge after examining the propriety of an agreement can not be implemented then the treaty would be contrary to public order and decency. Agreement is not only determined by the parties in the formulation of the agreement, but also determined by the good faith and decency, so in good faith and decency were also determines the content of the agreement. Thus a particular treaty agreement borrowing money if implemented not in good faith (in bad faith) such agreement is contrary to public order and morality and legal norms in force.